Host Transcriptome and Microbiota Signatures Prior to Immunization Profile Vaccine Humoral Responsiveness - Gonçalves, Elena; Guillén, Yolanda; Lama, Javier R.; Sanchez, Jorge; Brander, Christian; Paredes, Roger; Combadière, Behazine (Frontiers in Immunology, 2021)
The identification of new biomarkers is essential to predict responsiveness to vaccines. We investigated the whole-blood transcriptome and microbiome prior to immunization, in order to assess their involvement in induction of humoral responses two months later. We based our analyses on stool and skin microbiota, and blood transcriptome prior to immunization, in a randomized clinical study in which participants were vaccinated with the MVA-HIV clade B vaccine (MVA-B). We found that the levels of neutralizing antibody responses were correlated with abundance of Eubacterium in stool and Prevotella in skin. In addition, genus diversity and bacterial species abundance were also correlated with the expression of genes involved in B cell development prior to immunization and forecast strong responders to MVA-B. To our knowledge, this is the first study integrating host blood gene expression and microbiota that might open an avenue of research in this fieldand to optimize vaccination strategies and predict responsiveness to vaccines.